Islamic Education Holds Significant Importance In Reinforcing Moral And Ethical Values In The Context Of Globalization - Rahmat Lutfi Guefara; Ali Mu’tafi; Robingun Suyud El Syam (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2023)
Currently, Islamic education is crucial for developing knowledge based on faith and piety. It creates behavioral patterns that reflect a balance between physical and spiritual aspects, resulting in morally upright individuals. The decline in moral behavior among Muslims is a serious issue that requires significant attention. Islamic education contributes to the enhancement of faith and piety, which in turn shapes morally upright individuals, especially amidst the era of globalization that alters various aspects of life, including mindset. This study aims to understand the process of Islamic education as a means to actualize religious teachings, thereby strengthening the moral character of Muslims in the face of globalization. The research employs a qualitative method with a library research approach. The findings indicate that to address moral and ethical deviations in the era of globalization, it is necessary to revitalize Islamic education to strengthen the moral character of Muslims. The necessary steps include: 1) implementing a holistic and morality-based learning model, 2) revitalizing moral education, 3) revitalizing social education, and 4) revitalizing the role of technology.